Dampak Penggunaan Gadget Terhadap Konsentrasi dan Hasil Belajar Siswa Sekolah Dasar - Isnaeni Mutiara; Bagas Mukti Nasrowi (Advances In Education Journal, 2026)
Nowadays, digital technology is advancing so quickly that gadgets have become a normal part of everyday life, even for young children in elementary school. According to data from the Indonesian Internet Service Providers Association, internet usage among kids aged 5 to 12 years has been steadily rising. The core issue is that when children use gadgets too often without anyone watching over them, their ability to concentrate may suffer and their school performance may drop. The goal of this study is to examine how gadget use affects both the concentration and academic results of elementary school students. This research uses a library study approach with qualitative methods. Information was gathered by reviewing various academic sources such as journals and books. The data were then analyzed using qualitative content analysis, which involves reducing the data, presenting it, and drawing conclusions. The findings indicate that gadget use has two different sides. On the positive side, gadgets make it easier for students to access digital learning materials. On the negative side, using gadgets excessively without supervision tends to lower concentration and reduce learning outcomes because students spend less time on effective studying. The consequences include falling grades and becoming dependent on gadgets. In conclusion, gadgets are not automatically harmful. It all depends on how they are used and how much guidance children receive from their parents and teachers.